Pengaruh Iklim Organisasi, Budaya Organisasi Dan Lingkungan Kerja Terhadap Produktivitas Karyawan (Studi Pada PT Perkebunan Nusantara III Bagian operasional SDM Medan) - Rifqah Tiara Nazari Harahap; Kartini Harahap (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
These days, kelp sawmills are a significant contributor to the national economy as well as a dynamic force in the international business community. When it comes to the growth and development of the Indonesian economy, the agricultural sector is one of the most important players. In today’s enterprises, there is still a significant problem with worker productivity that has to be addressed. When formulating plans to increase employee productivity, a firm needs to take into consideration the climate, culture, and geography of the surrounding working environment. The purpose of this study was to learn how organizational climate, organizational culture, and organizational environment all affected productivity at the Strategic Development and Management division (SDM) of PT Perkebunan Nusantara III Medan. Specifically, the study wanted to determine how organizational climate affected productivity at SDM, how organizational culture affected productivity at SDM, and how organizational environment affected productivity at SDM. A quantitative approach was used for this investigation. Primary data and secondary data are the two types of data that were used in this research project. Participants in this research come from the Operational Services Division of PT Perkebunan Nusantara III Medan. They are the sample population for this investigation. In all, there were 35 people who took part in the survey that was used for this research. A method of taking a random sample known as non probability sampling is used in the sampling process. A Likert scale will be used as the information gathering method for the postcards that will be distributed. The version 26 of the statistical package SPSS is used for the analysis. The assumptions test, the linear regression analysis test, the parsimony test, the simultaneous analysis test, and the coefficient determination test are some examples of the several types of tests that may be used to analyze data. According to the results of this research, each of the independent factors, such as organizational climate, organizational culture, and workplace environment, have a simultaneous and partial influence on worker productivity Y. According to the R values presented above, which are also referred to as coefficient determination coefficients, the organizational climate (X1), organizational culture (X2), and work environment (X3) have a combined 70% effect on worker productivity (Y), whereas the remaining 30% is influenced by factors that are not included in the variables that were investigated in this study.